2019
DOI: 10.33545/pathol.2019.v2.i2f.125
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of semen parameters in male partners of infertile couples attending rural medical college

Abstract: Background: Infertility is a condition with psychological, economic, medical implications resulting in trauma, stress, particularly in a social set-up, with a strong emphasis on child-bearing. The prevalence of infertility in the general population is 8-12% worldwide. Of this, the male factor is responsible for 40-50%.Semen analysis is an indispensable diagnostic tool in the evaluation of the male partners of infertile couples. Materials and Method: Seminal fluid from the male partners was analysed in the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(28 reference statements)
2
0
0
Order By: Relevance
“…Such variability might be due to the dissimilar composition of the studied populations, mostly to the severity of the male factor.The observed sperm motility in the present study is comparable with those reported in other studies of infertile men with oligozoospermia (26%) (Shah et al, 2020) or Ghanaian sub-fertile men (23%) (Blay et al, 2020). In another study, about 25% of men from infertile couples had motility of about 32% (Shekha et al, 2019). Although there is no known critical age limit for gamete production in men, evidence suggests that there are declines in semen quality (e.g., volume, motility, and morphology) and male fertility associated with increasing male age (Andolz et al, 1999;Girsh et al, 2008;Dain et al, 2011;Zhu et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Such variability might be due to the dissimilar composition of the studied populations, mostly to the severity of the male factor.The observed sperm motility in the present study is comparable with those reported in other studies of infertile men with oligozoospermia (26%) (Shah et al, 2020) or Ghanaian sub-fertile men (23%) (Blay et al, 2020). In another study, about 25% of men from infertile couples had motility of about 32% (Shekha et al, 2019). Although there is no known critical age limit for gamete production in men, evidence suggests that there are declines in semen quality (e.g., volume, motility, and morphology) and male fertility associated with increasing male age (Andolz et al, 1999;Girsh et al, 2008;Dain et al, 2011;Zhu et al, 2011).…”
Section: Discussionsupporting
confidence: 91%
“…However, the sperm fertilizing capacity of both groups during ICSI was similar in terms of fertilization rates. Similar variations in ejaculated semen volume, sperm concentration, and sperm motility have been reported earlier in OAZ (Micic et al, 2019) and NZ (Shekha et al, 2019) males who underwent infertility treatment. In the present study, semen volume in sub-fertile Indian patients with oligoasthenozoospermic and normozoospermic semen quality constituted 2.64±0.23 and 2.14±0.16 ml, respectively.…”
Section: Discussionsupporting
confidence: 86%